Colorectal cancer-derived extracellular vesicles: at the crossroads of the tumor microenvironment and gut microbiota - Li, Hao; Zhang, Wei; Yan, Wenhui; Wang, Kun; Chen, Si; Li, Yamao; Sheng, Anzhi; Shang, Anquan; Zeng, Bingjie (Frontiers in Immunology, 2026)
Colorectal cancer (CRC) remains a leading cause of cancer-related morbidity and mortality worldwide. The clinical treatment faces multiple challenges of significant tumor heterogeneity, prevalence of chemo-resistance, low response rate to immunotherapy, and the impact of the patient’s intestinal microenvironment. Recent studies have shown that extracellular vesicles (EVs), as important information transfer carriers for regulating tumorigenesis and development, play a key role in mediating the complex regulatory network of the gut microbiota-tumor microenvironment (TME). Based on current research advances, our review systematically elucidates how CRC-derived EVs function as dynamic molecular messengers, mediating bidirectional interactions between the TME and the gut microbiota. It also provides a comprehensive outline of EV biogenesis and the key signaling pathways regulated by their diverse molecular cargo. It further delineates how these pathways act in concert to promote the formation of an immunosuppressive microenvironment, drive tumor metastasis, and confer therapy resistance. This review aims to provide a coherent theoretical framework for understanding CRC progression and drug resistance, to offer a scientific rationale for novel therapies targeting CRC-derived EVs, and to highlight future research directions essential for overcoming methodological bottlenecks, deciphering complex interaction networks, and advancing clinical translation.